2022
DOI: 10.1101/2022.11.27.516868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RBPMS promotes contractile smooth muscle splicing and alters phenotypic behaviour of human embryonic stem cell derived vascular smooth muscle cells

Abstract: Differentiated Vascular Smooth Muscle Cells (VSMCs) express a unique network of splice isoforms (smooth muscle specific alternative splicing - SM-AS) in functionally critical genes including those comprising the contractile machinery. We previously described RNA Binding Protein Multiple Splicing (RBPMS) as a potent driver of contractile, aortic tissue like SM-AS in VSMCs using rodent models. What is unknown is how RBPMS affects VSMC phenotype and behaviour. Here, we use human embryonic stem cell-derived VSMCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…However, in human breast cancer cells RBFOX1 promoted skipping of the same exon, as part of epithelial-mesenchymal transition (Li et al, 2018). Other lines of evidence also suggest widespread functional cooperation of RBPMS and RBFOX proteins including: enrichment around RBPMS-regulated exons not only of RBPMS dual CAC binding motifs but also of RBFOX binding GCAUG motifs (Jacob et al, 2022); the identification of a GCAUG containing motif as the top intronic binding site for RBPMS in ES cells (Bartsch et al, 2021); and the association of both RBFOX and RBPMS binding motifs with ERG (E26 related gene protein)-repressed exons in HeLa cells (Saulnier et al, 2021). Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, in human breast cancer cells RBFOX1 promoted skipping of the same exon, as part of epithelial-mesenchymal transition (Li et al, 2018). Other lines of evidence also suggest widespread functional cooperation of RBPMS and RBFOX proteins including: enrichment around RBPMS-regulated exons not only of RBPMS dual CAC binding motifs but also of RBFOX binding GCAUG motifs (Jacob et al, 2022); the identification of a GCAUG containing motif as the top intronic binding site for RBPMS in ES cells (Bartsch et al, 2021); and the association of both RBFOX and RBPMS binding motifs with ERG (E26 related gene protein)-repressed exons in HeLa cells (Saulnier et al, 2021). Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%